2010
DOI: 10.1055/s-0030-1248420
|View full text |Cite
|
Sign up to set email alerts
|

Akzeptanz- und achtsamkeitsbasiertes Gruppenkonzept für Patienten mit fortgeschrittenem Diabetes Typ 2: Konzept und praktische Erfahrungen

Abstract: Patients with type 2 diabetes mellitus and early diabetic nephropathy have a poor disease-related prognosis; furthermore these patients are often also mentally stressed. We investigated an acceptance- and mindfulness-based group intervention for these patients in addition to regular medical therapy. Both intervention program and descriptive outcomes of patients' evaluation are presented. A total of 51 patients attended the groups. Patients reported developing a mindfulness attitude towards life during the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…With respect to the worries about diabetes, it was found that increasing the patients' awareness could reduce their anxiety and concern, increase their QOL, and reduce their blood pressure level, depression, and intrusive thoughts, and improve their sleep quality. In most studies, the training was given by specialists and nurses,[181920] and no study was found to assess the effect of peer groups on the concern and worries of elderly patients with diabetes. In a long-term follow-up of 2, 3, and 4 years, Ridge et al .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the worries about diabetes, it was found that increasing the patients' awareness could reduce their anxiety and concern, increase their QOL, and reduce their blood pressure level, depression, and intrusive thoughts, and improve their sleep quality. In most studies, the training was given by specialists and nurses,[181920] and no study was found to assess the effect of peer groups on the concern and worries of elderly patients with diabetes. In a long-term follow-up of 2, 3, and 4 years, Ridge et al .…”
Section: Discussionmentioning
confidence: 99%
“…Over time, this may result in less arousal, reduced emotional distress, and more effective health behaviors. For the purpose of our study, MBSR was adapted (12) by including practices for difficult thoughts and feelings related to diabetes. Participants met once weekly in groups of 6–10 and for a booster session after 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The abstracts in English of six studies published in Farsi [20][21][22][23][24][25] and two studies published in German [26,27] were screened for inclusion, and all included at this stage. The Google Translator tool was used to translate the Farsi studies [20][21][22][23][24][25] for full-text screening.…”
Section: Study Selection and Inclusion Criteriamentioning
confidence: 99%
“…The accuracy of Google Translate was found to be around 90% [28], and a native speaker (AR) sought to sense-check the accuracy of the verbatim translation and made any corrections to the text as required. The German studies [26,27] were translated into English by a bilingual speaker known to an author and fluent in both languages. Six studies [20][21][22][23][24][25] were translated from Farsi to English by a native Farsi speaker also fluent in English (AR).…”
Section: Study Selection and Inclusion Criteriamentioning
confidence: 99%